The role of the concept of sustainable development and its indicators in a study on the progress of the new UN goals - Paulina Szyja (Economic and Environmental Studies (E&ES), 2018)
Nowadays the world is facing a serious problem related to climate change and its repercussion for human beings. At the same time, world societies are struggling with the consequences of the last economic crisis. These issues have not escaped the attention of the United Nations, and therefore in 2015 the organization adopted 17 goals to improve the social, economic and environmental situation. The Sustainable Development Goals are not the first priorities announced for the world. In 2000, the Millennium Development Goals were adopted. They dealt with important issues of the day, encouraging the global community to take necessary actions. This paper addresses two issues. Firstly, it describes the evolution of the range of adopted goals to improve the socio-economic situation of people, taking into consideration the relation with the concept of sustainable development. Secondly, it uses the indicators as the main instruments to assess the progress in achieving accepted aims.
Keywords: O10; O20; Q56; 330; development; Millennium Development Goals; progress; sustainable development; Sustainable Development Goals; sustainable development indicators